Methods of teaching medical ethics at the University of Nottingham - Fentem, P. H. (Journal of medical ethics, 1985)
Medical ethics has been described as a thread woven into the fabric of the Nottingham curriculum. There exist a wide variety of relevant learning experiences, occurring at intervals throughout each of the five years of the course. The introduction of the students to clinical method from the start creates the need for early consideration of ethical aspects of professional behaviour and this in turn stimulates spontaneous discussion and inquiry amongst the students. The school has chosen to rely on having a sufficient number of medical teachers from various disciplines willing to discuss in all the necessary detail their own clinical decisions.